1999
DOI: 10.1016/s0014-5793(99)00347-6
|View full text |Cite
|
Sign up to set email alerts
|

Energy‐dependent transformation of the catalytic activities of the mitochondrial F0·F1‐ATP synthase

Abstract: The ADP(Mg P+ )-deactivated, azide-trapped F H WF IATPase of coupled submitochondrial particles is capable of ATP synthesis being incapable of ATP hydrolysis and ATP-dependent v" W r + generation [FEBS Lett. (1995) 366, 29^32]. This puzzling phenomenon was studied further. No ATPase activity of the submitochondrial particles catalyzing succinate-supported oxidative phosphorylation in the presence of azide was observed when ATP was added to the assay mixture after an uncoupler. Rapid ATP hydrolysis was detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
19
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 29 publications
4
19
0
Order By: Relevance
“…It is only certain that the activation probability was the highest in the presence of both ADP and P i . A similar finding was reported by Vinogradov and colleagues (29,30), that is, a submitochondrial particle containing the FoF 1 -ATPase showed a higher ATP-hydrolysis activity after transient charging of the membrane potential. The most plausible explanation is that when F 1 is rotated in the ATP-synthetic direction in the presence of the ADP and P i , the F 1 follows the ATP synthesis pathway to be efficiently activated.…”
Section: Angle Deviation Between the ␥-Subunit And The Magnetic Beadssupporting
confidence: 87%
“…It is only certain that the activation probability was the highest in the presence of both ADP and P i . A similar finding was reported by Vinogradov and colleagues (29,30), that is, a submitochondrial particle containing the FoF 1 -ATPase showed a higher ATP-hydrolysis activity after transient charging of the membrane potential. The most plausible explanation is that when F 1 is rotated in the ATP-synthetic direction in the presence of the ADP and P i , the F 1 follows the ATP synthesis pathway to be efficiently activated.…”
Section: Angle Deviation Between the ␥-Subunit And The Magnetic Beadssupporting
confidence: 87%
“…We concluded that CF 0 F 1 did not catalyze uncoupled ATP hydrolysis and that, therefore, no corrections for uncoupled ATP hydrolysis were required. For MF 0 F 1 as well, the presence of a strong preactivation by Δμ H þ has been reported (24). However, with MF 0 F 1 small rates of ATP hydrolysis were detected in the presence of nigericin at Q values ≥1.87, and these rates increased with increasing Q value.…”
Section: Resultsmentioning
confidence: 79%
“…Presumably, the inhibited structure represents one of the most stable forms of this enzyme, and is separated by a relatively small activation barrier from the major kinetic pathway of the hydrolysis reaction. In this regard, it is worth noting that MgADP inhibition does not operate during synthesis (Boyer 1997(Boyer , 2000, and synthesis renders inhibited enzyme back to a form capable of hydrolysis (Galkin & Vinogradov 1999). Free energy obtained by clockwise rotation of g will lift the enzyme from the bottom of the potential well back to the major pathway, or to a possibly di¡erent path for the synthesis.…”
Section: (A) Three Modes Of Hydrolysis Reactionmentioning
confidence: 99%